The Influence of Experiential Marketing and Service Quality on Repurchase Intention - Sulastri, R. Ela (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
The study entitled The Influence of Experiential Marketing and Service Quality on Repurchase Interest is a study of how much influence experiential marketing is carried out by entertainment venue managers and the quality of service carried out to support increased visitors as an impact of repurchase interest carried out by visitors. This study uses a descriptive and verification research design, with a quantitative research method. Descriptive testing in this study is done by using continuous line analysis and its verification analysis using path analysis. The results of the analysis show that experiential marketing carried out by managers is included in the good category, this is supported by the quality of service provided by managers according to respondents' responses is good. Based on the analysis carried out, shows that the relationship between the variables studied has a positive relationship, and experiential marketing and service quality both simultaneously and partially have a significant effect on consumer repurchase interest. Of the two variables studied, experiential marketing has a greater influence than service quality on the repurchase interest of visitors to Jans Park Jatinangor.